2020
DOI: 10.15241/dl.10.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Research Identity Development of Counselor Education Doctoral Students: A Grounded Theory

Abstract: We present a grounded theory based on interviews with 11 counselor education doctoral students (CEDS) regarding their research identity development. Findings reflect the process-oriented nature of research identity development and the influence of program design, research content knowledge, experiential learning, and self-efficacy on this process. Based on our findings, we emphasize the importance of mentorship and faculty conducting their own research as a way to model the research process. Additionally, our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
1
13
0
Order By: Relevance
“…Research mentorship (specifically that of faculty members) was identified as the most critical resource for doctoral students, corroborating previous studies exploring doctoral students’ research development (e.g., Borders et al., 2020; Limberg et al., 2020). Faculty mentors provided a “walkthrough” of the entire publication and editorial feedback process, and helped their students set realistic expectations while providing encouragement and validation.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Research mentorship (specifically that of faculty members) was identified as the most critical resource for doctoral students, corroborating previous studies exploring doctoral students’ research development (e.g., Borders et al., 2020; Limberg et al., 2020). Faculty mentors provided a “walkthrough” of the entire publication and editorial feedback process, and helped their students set realistic expectations while providing encouragement and validation.…”
Section: Discussionsupporting
confidence: 86%
“…Doctoral students reported a sense of achievement and increased self‐efficacy after the publication and editorial feedback experiences. Having their manuscripts published—or submitted to journals for publication—was an experience of receiving “external validation,” which contributed to their confidence and motivation to further pursue research (Limberg et al., 2020, p. 497). Researchers have found that having concrete research experience and self‐confidence in one's research are positively associated with developing the students’ researcher identity (Lamar & Helm, 2017; Reisetter et al., 2004) and achieving enhanced scholarly productivity (Lambie & Vaccaro, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Lambie et al (2014) conducted an exploratory investigation to examine the relationships among doctoral students' research self-efficacy, interest in research, and research knowledge. This study led Limberg et al (2020) to investigate these relationships in a qualitative study in order to further understand how doctoral students experienced each variable. Alternatively, counseling researchers may implement an intervention study and then use a correlational design to further understand the relationships of the variables within the intervention.…”
Section: Utility and Applicability Of The Correlational Designmentioning
confidence: 99%